2017
DOI: 10.1093/femsec/fix084
|View full text |Cite
|
Sign up to set email alerts
|

In defence of Bacillus thuringiensis, the safest and most successful microbial insecticide available to humanity—a response to EFSA

Abstract: The Bacillus cereus group contains vertebrate pathogens such as B. anthracis and B. cereus and the invertebrate pathogen B. thuringiensis (Bt). Microbial biopesticides based on Bt are widely recognised as being among the safest and least environmentally damaging insecticidal products available. Nevertheless, a recent food-poisoning incident prompted a European Food Safety Authority review which argued that Bt poses a health risk equivalent to B. cereus, a causative agent of diarrhoea. However, a critical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 59 publications
2
59
0
3
Order By: Relevance
“…The high cost of Cry toxin production and specialization to invertebrate hosts could explain the excellent safety record of Bt ‐based biopesticides. Despite their close phylogenetic relationship to Bc isolates capable of causing diarrhoea (Raymond & Federici, ; Raymond, Johnston, et al., ; Raymond, Wyres, et al., ), growth in the vertebrate gut and vegetative production of enterotoxins are required for diarrhoeal food poisoning (Ceuppens et al., ), and production of Cry toxins is likely to hamper vegetative outgrowth considerably.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high cost of Cry toxin production and specialization to invertebrate hosts could explain the excellent safety record of Bt ‐based biopesticides. Despite their close phylogenetic relationship to Bc isolates capable of causing diarrhoea (Raymond & Federici, ; Raymond, Johnston, et al., ; Raymond, Wyres, et al., ), growth in the vertebrate gut and vegetative production of enterotoxins are required for diarrhoeal food poisoning (Ceuppens et al., ), and production of Cry toxins is likely to hamper vegetative outgrowth considerably.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, Bt is not a monophyletic group, and several divergent clades defined by multilocus sequence typing (MLST) or genomic data contain Bt isolates with Cry inclusions (Raymond, Wyres, et al., ). The taxonomy of the B. cereus group , and of Bt within it, is controversial, while accurate and informative species delineation has important economic implications (EFSA , Raymond & Federici, ). The licensing and “safe” status of Bt as a biological control agent that can be applied to vegetable crops are partly dependent on its biological distinctiveness from human pathogenic Bc and Ba .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Bt plants are capable of producing proteins from the insecticidal bacteria, Bacillus thuringiensis (Bt), that creates resistance to attacks from specific pests. Studies with Bt plants have been conducted for half a century, and demonstrated that they are efficient biopesticides and are harmless to humans and the environment (6). However, the products based on Bt are not prominent in the insecticide market, principally due to problems with the loss of stability, the absence of translocation in the plants, the limited action spectrum and their rapid degradation due to ultra-violet light.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic or facultative anaerobic, catalase-positive and sporeproducing Gram-positive bacteria represent this genus, which may be present in both aquatic and terrestrial environments. It includes species of ecological importance, such as B. thuringiensis (Raymond and Federici, 2017) and medical relevance, for example, B. antracis (Banada et al, 2017) and B. cereus (Owusu-Kwarteng et al, 2017). This genus also includes B. pumilus and B. licheniformis, being the last increasingly recognized as a human pathogen, causing serious infections in immunocompromised patients, food poisoning and ocular infections (Mohapatra and La Dut, 2012).…”
mentioning
confidence: 99%